Global patterns and associated drivers of priming effect in response to nutrient addition. (February 2021) - Feng, Jiguang; Zhu, Biao
Abstract: Priming effect (PE) induced by inputs of fresh carbon plays crucial roles in soil organic matter decomposition and terrestrial carbon cycling. Priming effect is considered to be largely influenced by nutrient availability, but the global-scale patterns reflecting how nutrient addition affects PE and the controlling factors for such effects remain unclear. By conducting a meta-analysis of 355 observations from 71 studies worldwide, we explored the global patterns and associated drivers of PE responding to nutrient addition. Results showed that, overall, nitrogen (N) and nitrogen plus phosphorus (NP) addition significantly decreased PE, whereas phosphorus (P) addition had minimal effect on PE ( P > 0.05). The effects of N and NP addition on PE varied with ecosystem, experiment and carbon substrate types. Specifically, N and NP addition generally decreased PE in forest and grassland, but did not change PE in cropland. Among experiment types, such negative effects occurred in incubation experiments, but not in pot experiments. Between carbon substrate forms (i.e., containing the added nutrient or not), N and NP addition only decreased PE in groups of carbon substrates that did not contain the added mineral nutrient. Moreover, the effect of N addition on PE depended primarily on the N limitation of microbial respiration across sties, with such effect increasing significantly with microbial N limitation (indicated by microbial respiration response to N addition and C:N imbalance between microbes and resources). Based on this relationship, we proposed a conceptual model linking microbial N mining and stoichiometric decomposition hypotheses, in which the former dominates in soils with less microbial N limitation and the latter dominates in soils with relatively higher microbial N limitation. Our findings imply that N deposition may benefit soil carbon sequestration via suppressing PE, and highlight the need for field studies investigating the effects of nutrient addition on PE in the rhizosphere and in the subsoil. Highlights: We conducted a global meta-analysis of how nutrient addition affects soil priming. N and NP addition decreased priming, while P addition had minimal effect on it. N- and NP-addition effects on priming varied with ecosystem, experiment and substrate types. Microbial N limitation primarily controls priming in response to N addition. We linked the N mining and stoichiometric decomposition hypotheses at a large scale.